1981
DOI: 10.1037/0003-066x.36.7.730
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive psychology as ideology.

Abstract: A critical analysis of some of the major work in cognitive social, personality, and developmental psychology is offered. The author argues that cognitivism, by virtue of the primacy it gives to the individual knower, to subjective determinants of behavior, and to formal cognitive operations, represents a set of values and interests that reproduce and reaffirm the existing nature of the social order. But the joining of cognitive psychology with ideology is not simply intended to unmask the values carried by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
20

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(168 citation statements)
references
References 55 publications
0
148
0
20
Order By: Relevance
“…Examples of these realities include the one billion people currently living in slums, creating cauldrons of conflict and destabilization, and the deleterious effects of burning coal on air quality in one location and on population health in other parts of the world. Thus, Sampson (1981) exhorted psychologists to avoid the biases of subjectivism and individualism in their theories, whereby objective realities are ignored or cognitively diminished in the minds of individual "knowers," often to the detriment of their well-being. Wohlwill (1973) New conceptualizations of human response to ecological, social, and technological change are needed, particularly those that (a) address the links between local and global events, (b) encompass collective as well as individual efforts to cope with impending threats, and (c) incorporate an extended rather than narrow time perspective.…”
Section: Psychological Perspectives On People-environment Relations Imentioning
confidence: 99%
“…Examples of these realities include the one billion people currently living in slums, creating cauldrons of conflict and destabilization, and the deleterious effects of burning coal on air quality in one location and on population health in other parts of the world. Thus, Sampson (1981) exhorted psychologists to avoid the biases of subjectivism and individualism in their theories, whereby objective realities are ignored or cognitively diminished in the minds of individual "knowers," often to the detriment of their well-being. Wohlwill (1973) New conceptualizations of human response to ecological, social, and technological change are needed, particularly those that (a) address the links between local and global events, (b) encompass collective as well as individual efforts to cope with impending threats, and (c) incorporate an extended rather than narrow time perspective.…”
Section: Psychological Perspectives On People-environment Relations Imentioning
confidence: 99%
“…The experiment yielded results supportive of these 3 predictions. The study also revealed some evidence of individual differences in social and cognitive strategies for coping with accountability.Many writers have criticized cognitive social psychology for its apparent indifference to the interpersonal and institutional settings within which people make judgments and choices (e.g., Gergen, 1982;Sampson, 1981). Although these critiques make important points, it is necessary to advance beyond metatheoretical position papers and to specify the particular ways in which interpersonal and institutional variables interact with cognitive tendencies of the perceiver to shape how people actually make up their minds.…”
mentioning
confidence: 99%
“…La dificultad a la hora de lograr esto es lo ha llevado a Ian Parker (2010) a abogar por la supresión de la psicología -de todo tipo de psicología, sea cual sea su orientación teórica y metodológica-en el análisis de la realidad social y de los problemas sociales desde posiciones de izquierdas o progresistas. Es más, creo que esa psicología social crítica y emancipadora es más necesaria aún hoy día que en el pasado, sobre todo porque si la psicología estuvo siempre al servicio del capitalismo (Sampson, 1977;1981), hoy día lo está aún más: psicologizando los problemas sociales y haciendo que los problemas que están teniendo millones de personas a causa de las injustas políticas neoliberales sean vistos como meros problemas personales de los individuos afectados, la psicología está haciendo un servicio realmente inestimable al nuevo capitalismo global (los desempleados no tienen trabajo porque no son capaces de adaptarse a las exigencias de la globalización; los delincuentes lo son porque tienen problemas personales, casi siempre relacionados con sus genes; quienes fracasan en la escuela se debe a su bajo CI…). Y de esta manera, los psicólogos están contribuyendo poderosamente a que la ciudadanía no perciba quiénes son los responsables reales de tales problemas y no le eche la culpa a las políticas de precarización laboral que está empeorando cada día más las condiciones de vida de cientos de millones de trabajadores y a las medidas de austeridad que tanto daño están haciendo a millones de personas y al propio crecimiento económico, incrementando las desigualdades hasta niveles realmente peligrosos y obscenos (Bauman, 2013(Bauman, /2014Blyth, 2013Blyth, /2014Ovejero, 2014;Piketty, 2013;Stuckler y Basu, 2013;Wilkinson, 2000Wilkinson, /2001Wilkinson y Pickett, 2009).…”
Section: Xv)unclassified